The Earth Topography 2022 (ETOPO 2022) global DEM dataset - M. MacFerrin; M. MacFerrin; C. Amante; C. Amante; K. Carignan; K. Carignan; M. Love; M. Love; E. Lim; E. Lim (Earth System Science Data)
Here we present Earth TOPOgraphy (ETOPO) 2022, the latest iteration of NOAA's global seamless topographic–bathymetric dataset. ETOPO1, NOAA's prior release at 1 arcmin resolution, has been a widely used benchmark global digital elevation model (DEM) since its initial release in 2009 (Amante and Eakins, 2009). Tsunami forecasting, modeling, and warning systems critically rely upon accurate topographic and bathymetric data to predict and reproduce water movement across global ocean surfaces, wave heights at the coastline, and subsequent land inundation. ETOPO 2022 is an updated topographic–bathymetric dataset at 15 arcsec global resolution that incorporates bare-Earth datasets with forests and buildings removed. ETOPO 2022 integrates more than a dozen source datasets for land topography, sea bathymetry, lake bathymetry, and ice-sheet bed elevation data, all of which have been carefully evaluated for quality, accuracy, and seamless integration. We evaluate the relative and absolute vertical accuracies of all land-elevation input datasets, as well as the final ETOPO 2022 tiles, using a geographically optimized, independent database of bare-Earth elevation photons from NASA's ICESat-2 satellite mission over the calendar year 2021. Measured against more than 960 billion lidar measurements from ICESat-2 that span nearly the entire globe, ETOPO 2022 measures a global RMSE of 7.17 m. ETOPO 2022 is publicly available in both ice surface and bedrock versions that portray either the top layer of the ice sheets covering Greenland and Antarctica or the bedrock below, and both versions are also available in GeoTIFF and NetCDF formats in 15×15° tiles, as well as global tiles at 30 and 60 arcsec resolutions. ETOPO 2022 provides a new publicly available seamless, globally validated elevation dataset to meet the present and future needs of the scientific global hazard and mapping communities. Datasets for the ETOPO 2022 15 Arc-Second Global Relief Model are available at https://doi.org/10.25921/fd45-gt74 (NOAA National Centers for Environmental Information, 2022).